Panyandra Rekasaning Perempuan: The Sacrifice Of A Housewife In The Novel Srengenge Tengange - Fasichalisna, Zianna; Retno Utami , Respati (Yayasan Mentari Madani, 2024)
Domestic violence is one of the most common cases in Indonesia. This was later made into a novel, namely Novell Srengenge Tengange by Narko Sodrun Budiman. The consequences of this violence were conveyed through the panyandra rekasaning women because women sacrificed a lot. Therefore, this research uses stylistic theory to find out the meaning behind the pannyandra. This study uses qualitative methods with data analysis techniques using literature study techniques. This presumably concerns the sacrifice of a housewife in Srengenge Tengange novel which is conveyed through panyandra. Based on the explanation above, it can be seen that the role of men in the household is very important. The impact of domestic violence itself varies, including what was experienced by the character Anisa, namely the emergence of trauma, lack of confidence, and difficulties empowering oneself. Therefore, it is necessary to have responsibilities that must be carried out and fulfilled so that household life can run well